THE IMPACT OF ISLAMIC FINANCING PRODUCTS ON ISLAMIC BANKS PROFITABILITY: CASE OF AL RAYAN BANK (QATAR) - Moustapha, Larabi; Nadir , Troubia (I-iECONS e-proceedings, 2023)
This study aims to determine the effect of Musharaka, Murabaha, Istisna’a and Ijarah financing on the profitability of Al Rayan Islamic Bank. This research uses Quarterly data of Al Rayan Bank for 2011Q1-2023Q1. The data is taken from the financial statements of income and statements of financial position. The variables used in this study are independent variables, Musharaka, Murabaha, Istisna’a and Ijarah financing. While the dependent variable is, the Islamic bank's profitability measured by Return on Equity (ROE).The study used ARDL and Error Correction Models to analyze the short and long-term relationships between variables. Data collected were analyzed by using EViews10 software. ARDL bounds test findings shown that there is a cointegration relationship between bank profitability and Islamic financing Products variables in the long run. The results of the long-run analysis show that Musharaka financing has a positive and significant effect on ROE at the 5% level. Murabaha financing has a negative and significant effect on ROE. Meanwhile, the Istisna’a and Ijarah variables have no significant effect on ROE. The short run dynamics show that there is a negative and significant effect of Murabaha and Ijarah financing on the profitability of the Islamic bank, while lagged value of Murabaha LMUR(-1) has a positive and significant effect on the profitability index of the Islamic bank. Simultaneously, there is no relationship and effect of Musharaka and Istisna’a on the profitability of the Islamic bank in the short term.